Disproportionate impact of the COVID-19 pandemic on socially vulnerable communities: the case of Jane and Finch in Toronto, Ontario - Movahedi Nia, Zahra; Prescod, Cheryl; Westin, Michelle; Perkins, Patricia; Goitom, Mary; Fevrier, Kesha; Bawa, Sylvia; Kong, Jude Dzevela (Frontiers in Public Health, 2025)
ObjectiveThis work aims to study the disproportionate impact of the COVID-19 pandemic on the Jane and Finch community, one of the socially vulnerable neighborhoods in the Greater Toronto Area (GTA), Ontario, Canada, in terms of morbidity, mortality, and healthcare services.MethodologyA dataset provided by the Black Creek Community Health Centre (BCCHC), gathered from different health-related portals, covering various health statistics during COVID-19, namely, COVID-19 number of cases, hospitalizations, deaths, percentage of vaccination with one-, two-, and three-dose(s), Primary and Preventive Care (PPC) visits which include fecal and pap-smear cancer tests, and percentage of completed Imaging, Procedures, and Surgeries (IPS) which include the number of patients waiting for surgery were studied using statistical analysis. Underserved communities in the Peel, York, and City of Toronto regions were recognized using the Ontario Marginalized Index (ON-Marg). The Jane and Finch community was selected from the fifth quintile of the ON-Marg index and compared with the remaining locations (first to fourth ON-Marg quantiles) using Kruskal-Wallis, Mann–Whitney u, and t-tests. The Gini index was used to understand the inequality of the health parameters among the selected neighborhoods. Local Indicator of Spatial Association (LISA) was used to detect the neighborhoods with significantly higher numbers of COVID-19 cases, hospitalizations, and mortalities.ResultsThe Jane and Finch community had a significantly (p < 0.0001) higher number of COVID-19 cases, hospitalizations, and mortalities. The significance and cluster analysis of LISA also extracted the Jane and Finch community as one of the hotspots with significantly higher COVID-19 infection, hospitalization, and death. The percentage of the third-dose vaccination was significantly lower for the Jane and Finch community (p = 0.0004). The number of patients during the COVID-19 pandemic versus before that decreased significantly more for pop-smear tests (p = 0.041) and surgery waitlists (p = 0.037) for the Jane and Finch community.ConclusionAs one of the most socially vulnerable communities of GTA, the Jane and Finch community has endured a heavier burden of the disease during the COVID-19 pandemic. This work aims to help the Jane and Finch community recover faster by shedding light on health areas in which it has suffered more from the COVID-19 outcomes.